Genomic Risk Factors Driving Immune-Mediated Delayed Drug Hypersensitivity Reactions - Li, Yueran; Deshpande, Pooja; Hertzman, Rebecca J.; Palubinsky, Amy M.; Gibson, Andrew; Phillips, Elizabeth J. (Frontiers in Genetics, 2021)
Adverse drug reactions (ADRs) remain associated with significant mortality. Delayed hypersensitivity reactions (DHRs) that occur greater than six hours following drug administration are T-cell mediated with many severe DHRs now associated with human leukocyte antigen (HLA) risk alleles, opening pathways for clinical prediction and prevention. However, incomplete negative predictive value (NPV), low positive predictive value (PPV) and a large number needed to test (NNT) to prevent one case has practically prevented large scale and cost-effective screening implementation. Additional factors outside of HLA contributing to risk of severe T-cell mediated DHRs include variation in drug metabolism, T-cell receptor (TCR) specificity, and most recently HLA-presented immunopeptidome-processing efficiencies via endoplasmic reticulum aminopeptidase (ERAP). Active research continues towards identification of other highly polymorphic factors likely to impose risk. These include those previously associated with T-cell mediated HLA-associated infectious or auto-immune disease such as Killer cell immunoglobulin-like receptors (KIR), epistatically linked with HLA class I to regulate NK- and T-cell mediated cytotoxic degranulation, and co-inhibitory signaling pathways for which therapeutic blockade in cancer immunotherapy is now associated with an increased incidence of DHRs. As such the field now recognizes that susceptibility is not simply a static product of genetics, but that individuals may experience dynamic risk, skewed toward immune activation through therapeutic interventions and epigenetic modifications driven by ecological exposures. This review provides an updated overview of current and proposed genetic factors thought to predispose risk for severe T-cell mediated DHRs.